The Effect of Saline and Non-Saline Soil Conditions on Yield and Nutritional Characteristics of Some Perennial Legumes Forages - Süleyman Temel; Bilal Keskin; Uğur Şimşek; İbrahim Hakkı Yılmaz (Journal of Agricultural Sciences)
Salinity is one of the important environmental stress factors restricting agricultural productivity and sustainability, particularly in arid and semi-arid regions. In the evaluation of saline soils, growing of salt tolerant or resistant plants is recently a widespread implementation. The aim of this study was to compare some yield and nutritional properties of alfalfa Medicago sativa L. , sainfoin Onobrychis sativa Lam. and bird’s foot trefoil Lotus corniculatus L. species cultivated in extreme saline-soil 9.80 EC dS m-1 and non-saline soil 0.43 EC dS m-1 conditions. For this purpose, this research was conducted in randomized blocks design with three replications on the Iğdır Plain, located in eastern Turkey, between the years of 2011-2013. Plants were sown under irrigable conditions in 2011, and data were obtained from the examined plants during three years including the year of sowing. In the study, leaf area index LAI , crude protein CP , fresh hay and hay yields differed significantly P